2012
DOI: 10.1016/j.jtcvs.2011.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin-collagen sponge reduces sternal wound complications after heart surgery: A controlled, prospectively randomized, double-blind study

Abstract: Routine prophylactic retrosternal use of a gentamicin-collagen sponge in patients undergoing cardiac surgery significantly reduces deep sternal wound infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 21 publications
2
86
1
3
Order By: Relevance
“…Some studies have reported that an antibiotic-collagen sponge was effective for the prevention of DSWI. However, the results from different studies have been controversial (12,13,28,29). In this study, we showed that the group treated with intravenous antibiotic, sternal debridement and flap reconstruction had a better prognosis than the group treated with intravenous antibiotic and sternal debridement (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 80%
“…Some studies have reported that an antibiotic-collagen sponge was effective for the prevention of DSWI. However, the results from different studies have been controversial (12,13,28,29). In this study, we showed that the group treated with intravenous antibiotic, sternal debridement and flap reconstruction had a better prognosis than the group treated with intravenous antibiotic and sternal debridement (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 80%
“…Three of these trials demonstrated a decrease in SSIs and one showed no difference. [10][11][12][13][14] A recent meta-analysis combining these trials concluded that the risk of deep sternal wound infection was significantly lower in patients who received a gentamicin collagen sponge than in patients who did not (RR, 0.62 [95% CI, 0.39-0.97]) despite significant heterogeneity among the trials. 15 Hence, numerous studies with their significant findings advocate the use of topical antibiotic in reducing the rate of SSSI while others refute the routine use of topical antibiotics.…”
Section: Incidence Of Superficial Surgical Site Infection (Sssi)mentioning
confidence: 99%
“…15,16 These findings were confirmed with another prospective randomized controlled trial in 2012 showing infection reduction from 3.5% to 0.56%. 39 However, 2 randomized controlled trials in 2005 and 2010 failed to show a significant change in infection with topical antibiotics.…”
Section: 3046mentioning
confidence: 99%
“…Large, prospective, randomized trials have shown that the application of topical gentamicin directly to sternal wounds in cardiac surgery has led to a significant reduction in infection rates. 15,16,39 Similarly, the use of vancomycin powder in posterior spinal fusion for trauma has shown reduced infection rates from as much as 13% to as low as 0%. 17,19 The application of concentrated antibiotics directly to surgical wounds during nonspinal neurosurgical procedures has been more limited.…”
mentioning
confidence: 99%